Игра Эндера: [роман] / Орсон Скотт Кард - Кард Орсон Скотт (Азбука-бестселлер, 2022)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59794 / Цена: 465.00 / Сис.шифр: 84(4/8) / Авт.знак: К 21 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44